PENGARUH MINAT MASYARAKAT TERHADAP PRODUK RAHN PADA PEGADAIAN SYARIAH SEBELUM DAN SESUDAH PANDEMI COVID-19 - Reza Reza; Abid Ramadhan; Ahmad Suardi (Politeknik Raflesia Press, 2022)
Abstrack This study aims to determine the effect of public interest in rahn products before and after the Covid-19 pandemic at PT Pegadian Syariah Luwu Branch. The sample in this study were customers who used Rahn products before and after the Covid-19 pandemic. The data collection method used is a questionnaire sheet which is distributed directly to the customers of PT Pegadaian Syariah Luwu Branch. The population in this study are sharia pawnshop customers. The method in determining the sample used by the researcher is porposive sampling with the paired sample t-test analysis technique. The results of this study are that there is a significant difference in public interest in rahn products before and after the Covid-19 pandemic, where after the Covid-19 pandemic, public interest in rahn products has increased. Key Words: Covid-19, Community Interest, Rahn Products.